Edukasi Manajemen Waktu Dan Pelayanan Di Klinik Mandiri Untuk Perawat Dan Bidan Praktik Swasta - Rosmiati, Rosmiati; Vandika, Arnes Yuli (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Private practice nurses and midwives have dual responsibilities, both as clinical service providers and as time and service managers in the facilities they manage. Limited managerial skills, particularly in time management and service quality, can impact the quality of healthcare services provided. This community service activity aims to improve the knowledge and skills of private practice nurses and midwives in time management and excellent service delivery. The implementation method used was interactive education, simulations, and group discussions. Results showed an increase in participants' understanding of the principles of time efficiency, service flow, and effective communication. It is hoped that this activity will support the continuous improvement of service quality in private clinics.